Environment-friendly water-based anti-aging matte coating, matte black single-sided adhesive tape and preparation method thereof
By adding ultrafine nano-grade polyethylene wax to the matte oil coating of matte black single-sided tape, the problem of relative force aging climb between the silicone protective film and the coating is solved, and the aging resistance and environmental protection of the coating is improved.
Patent Information
- Application Number
- CN202510039603.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
After the existing matte black single-sided tape is transported at high temperature, the relative peeling force between the silicone protective film and the coating will climb, resulting in excessive relative force deformation and failure of die-cut parts when removing the protective film in the assembly section, resulting in material loss and economic losses.
The environmentally friendly water-resistant aging matte coating is adopted. By adding ultra-fine nano-grade polyethylene wax to the matte oil coating, it uses its low friction coefficient to prevent the coating from aging and climbing relative to the silicone protective film, achieving the purpose of aging resistance of the coating, and at the same time it plays a role in matte, scratch resistance, wear resistance and other functions.
After high temperature and high humidity aging, the relative force between the coating and the silicone protective film remains stable, and the relative force does not rise significantly before and after aging, which extends the shelf life of matte single-sided glue and improves its environmental protection.
Smart Images

Figure CN119875480A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to an environmentally friendly water-based aging-resistant matte coating, a matte black single-sided adhesive tape and a preparation method thereof. Background Art
[0002] Matt black single-sided tape is a common tape used in 3C electronic products. When using it, die-cutting manufacturers often need to stick a layer of silicone protective film on the coating surface to achieve the purpose of die-cutting transfer.
[0003] For example, a Chinese patent with publication number CN212894553U discloses a degassing matte black single-sided tape, which relates to the field of tape composite technology and includes a tape body, a release film is arranged at the bottom of the tape body, and a silicone protective film is arranged at the top, the tape body includes a PET film, an ink layer is arranged at the top of the PET film, and an acrylic adhesive layer is arranged at the bottom, the silicone protective film is attached to the top of the ink layer, the release film is attached to the bottom of the acrylic adhesive layer, and the upper surface of the ink layer is formed with concave and convex hexagons.
[0004] The tape has a good exhaust function, and because the upper surface of the ink layer is formed with concave and convex hexagons, slight grooves are formed, so that the silicone protective film can be peeled off more stably.
[0005] However, since the silicone protective film needs to be removed during downstream assembly, the process from die-cutting to assembly usually takes 1-3 months. In addition, due to the geographical differences between the die-cutting plant and the assembly plant, it may be transported by sea. The silicone protective film on the matte black tape of the die-cut parts will increase after long-term bonding and high-temperature sea transportation. As a result, when the protective film is removed in the assembly stage, the die-cut parts will deform and fail due to excessive relative force, causing material loss and economic losses.
[0006] In order to solve the above problems, the present invention provides an environmentally friendly water-based aging-resistant matte coating, a matte black single-sided adhesive tape and a preparation method thereof. Summary of the invention
[0007] The object of the present invention is to provide an environmentally friendly water-based aging-resistant matte coating, a matte black single-sided tape and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: an environmentally friendly water-based aging-resistant matte coating, comprising the following substances by weight: 46-68 parts of solvent; 15-35 parts of resin; 5-12 parts of PE wax emulsion; 3-5 parts of defoaming agent; 0.5-2 parts of dispersant; 2.5-6 parts of matting powder; 3-6 parts of thickener; and 5-8 parts of cross-linking agent.
[0009] More optimally, the particle size D50 of the PE wax emulsion is 0.1 μm.
[0010] Preferably, the solvent is deionized water.
[0011] More preferably, the matting agent is fumed silica.
[0012] More preferably, the thickener is water-based polyurethane.
[0013] More preferably, the cross-linking agent is a water-based isocyanate curing agent.
[0014] A matte black single-sided adhesive tape comprises any one of the above-mentioned environmentally friendly water-based aging-resistant matte coatings.
[0015] A method for preparing a matte black single-sided adhesive tape comprises the following steps:
[0016] S1, preparation of matt oil slurry: select quantitative polyester resin 1 and polyester resin 2, add solvent butanone and cyclohexanone, stir at a speed of 1100r / min for 25min; then add modified silica, stir at a speed of 1100r / min for 25min; after stirring evenly, use a sand mill to sand grind for 1-3H. During the sand grinding process, regularly take samples to test the particle size. When the particle size reaches the required specification, stop sand grinding to obtain matt oil slurry;
[0017] S2, applying corona on the surface of a black substrate with a thickness of 0.05 mm, with the corona power set to 2 kW; applying the obtained matte oil slurry on the surface of the black substrate by micro-concave or gravure process to obtain a matte black anti-scratch coating film;
[0018] S3, transferring a 25 μm acrylic film onto the 50 μm silicone release film, and laminating the film onto the non-matt oil coating surface of the matt black anti-scratch coating film, thereby obtaining a matt black anti-scratch tape;
[0019] S4, placing the obtained matte black anti-scratch tape in a constant temperature chamber at 50° C. for curing for 72 hours to obtain a finished product.
[0020] More preferably, the substrate is a black PET or PI film.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] (1) In the present invention, after the matte single-sided adhesive is aged at high temperature and high humidity, the relative force between the coating and the silicone protective film remains stable, and there is no obvious increase in the relative force before and after aging.
[0023] (2) In the present invention, ultrafine nano-scale polyethylene wax is added to the matt oil coating, and the low friction coefficient of the polyethylene wax is utilized to prevent the relative force between the coating and the silicone protective film from aging and climbing, thereby achieving the purpose of coating aging resistance, and at the same time playing the role of matting, anti-scratch, anti-wear, anti-polishing, anti-imprinting, anti-adhesion, anti-precipitation, thixotropy and the like.
[0024] (3) The matte single-sided adhesive prepared by the present invention is environmentally friendly, and the solvent used is water, which avoids the damage of organic solvents to the human body and the environment.
[0025] (4) The present invention adds ultrafine polyethylene wax to the matte oil coating and utilizes the low friction coefficient of the polyethylene wax to prevent the relative force between the coating and the silicone protective film from aging and climbing. At the same time, the polyethylene wax also has the effects of anti-adhesion, anti-precipitation, and thixotropy, which can increase the stability of the water-based matte oil and extend the shelf life. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 This is a schematic diagram of the structure of Example 1.
[0028] Among them, 1. Release film; 2. Pressure-sensitive adhesive; 3. Base material; 4. Anti-aging coating. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The adhesive tape structure obtained in the present invention is as follows Figure 1 As shown, it includes a release film, a pressure-sensitive adhesive, a substrate and an anti-aging coating from top to bottom. In addition, the present invention verifies the performance effect of the matte single-sided adhesive by preparing several embodiments and comparative examples.
[0031] The specific preparation steps include:
[0032] Step 1, preparation of matt oil slurry: select 20 parts of polyester resin 1 and 6 parts of polyester resin 2, add 50 parts of solvent butanone and 10 parts of cyclohexanone, and stir at a speed of 1100r / min for 25min; add 4 parts of modified silica, and stir at a speed of 1100r / min for 25min; after stirring evenly, use a sand mill to sand grind for 1-3H. During the sand grinding process, regularly sample and test the particle size. When the particle size reaches the required specification, stop sand grinding to obtain matt oil slurry.
[0033] Step 2: Preparation of matte black anti-scratch tape:
[0034] 1. Apply corona to the surface of black PET substrate with a thickness of 0.05mm, and set the corona power to 2kw.
[0035] 2. Using the micro-dimpled process, 2 μm of anti-scratch matt oil was coated on the corona surface of the above black PET substrate to obtain a matt black anti-scratch PET film.
[0036] 3. Transfer coat a 25 μm acrylic film on the 50 μm silicone release film and adhere it to the non-matt oil coating surface of the matt black scratch-resistant PET film to obtain a matt black scratch-resistant tape.
[0037] 4. Place the matte black anti-scratch tape in a constant temperature chamber at 50°C for aging and curing for 72 hours to obtain the finished product.
[0038] The specific weight parts of the substances in the examples and comparative examples are shown in Table 1.
[0039] Table 1 Weight percentage of substances in each embodiment and comparative example
[0040]
[0041] Among them, PE wax emulsion A is BASF WAX35 wax emulsion, Huabang high energy material HG-8005, BASF wax emulsion WAX26, and the particle size is <0.1μm.
[0042] PE wax emulsion B is Clariant water-based wax liquid W-19 with a particle size D50 of 20 μm.
[0043] The PE wax emulsion used in Example 01, Example 02, Comparative Example 02 and Comparative Example 03 is BASF WAX35 wax emulsion.
[0044] The PE wax emulsion used in Example 03 is Huabang High Energy Materials HG-8005.
[0045] Comparative Example 01 did not add PE wax emulsion.
[0046] The PE wax emulsion used in Comparative Example 04 is Clariant water-based wax liquid W-19.
[0047] The matte black anti-scratch tape was tested for performance, and the test results are shown in Table 2.
[0048] The basic properties of matte black single-sided adhesive are tested by the following instruments. If the test conditions are not specified, the following tests are all tested at room temperature 23℃-50%RH.
[0049] 1. 100-grid test: Use a 100-grid knife to scratch the matt oil coating surface of the sample ten times in the horizontal and vertical directions, and then use 3M Stick the transparent tape and press it with your fingers. After 1 minute, pull it vertically once. If the matt oil coating does not fall off, the test is OK. If the coating falls off, it is NG. The 100-grid knife scribing instrument is a product of Dongguan Maike Instrument Equipment Co., Ltd.
[0050] 2. Gloss test: Place the sample horizontally on the test table with the coating side facing up, and use a gloss meter to test the gloss value. Read the gloss value at an incident angle of 60°. Test three samples and take the arithmetic mean of the three test results as the gloss result. The gloss meter used is micro-TRI-gloss 20°60°85°4563 model from BYK, Germany.
[0051] 3. Anti-scratch performance test: Place the sample horizontally on the test table with the coating facing up, and use a gloss meter to test the gloss value Gu1; Place the test sample on an abrasion tester equipped with EF74 standard rubber, and rub the matt oil coating of the sample at a reciprocating speed of 60 times / minute under a gravity of 500 grams, and rub back and forth 50 times. After the friction is completed, test the gloss value Gu2 at the friction mark; Calculate the gloss difference before and after friction ΔGu=Gu2-Gu1; The rubber resistance test is tested using the A20-339A abrasion tester produced by Suzhou Huachuan Testing Instrument Co., Ltd.
[0052] 4. Relative peeling force of silicone protective film - pre-aging test: stick the adhesive surface of a 120mm long × 40mm wide matte black single-sided tape sample onto a stainless steel mirror steel plate (150mm long × 50mm wide × 2mm thick and surface roughness: 10nm±10nm) that meets the material requirements of the GB / T2792 peeling test steel plate;
[0053] Use a 2kg roller to roll the sample back and forth on the stainless steel mirror plate with the sample strip attached once at a speed of 300mm / min, then stick a 150mm long × 25mm wide silicone protective film to the coated surface of the matte black single-sided adhesive, and use a 2kg roller to roll the sample back and forth on the stainless steel mirror plate with the sample strip attached once at a speed of 300mm / min;
[0054] After standing for 20 minutes under the test environment (23°C-50% RH), a 180° peel strength test was performed using a stretching machine under the test environment (23°C-50% RH). The peeling speed was 300 mm / min, and the number of test samples was 3. The arithmetic mean of the 3 test results was taken as the peeling force result.
[0055] 5. Relative peeling force of silicone protective film - after aging test: stick the adhesive surface of the 120mm long × 40mm wide matte black single-sided tape sample to a stainless steel mirror steel plate (150mm long × 50mm wide × 2mm thick and surface roughness: 10nm±10nm) that meets the material requirements of the peeling test steel plate of GB / T2792;
[0056] Use a 2kg roller to roll the sample back and forth on the stainless steel mirror plate with the sample strip attached once at a speed of 300mm / min, then stick a 150mm long × 25mm wide silicone protective film to the coated surface of the matte black single-sided adhesive, and use a 2kg roller to roll the sample back and forth on the stainless steel mirror plate with the sample strip attached once at a speed of 300mm / min;
[0057] Place it in an environmental test box (85℃-85%RH) for aging, take it out after aging for 72 hours, and let it stand in the test environment (23℃-50%RH) for 24 hours. Then use a tensile machine to perform a 180° peel strength test in the test environment (23℃-50%RH). The peeling speed is 300mm / min. The number of test samples is 3, and the arithmetic mean of the 3 test results is taken as the peeling force result.
[0058] Table 2 Test results of various embodiments and comparative examples
[0059]
[0060]
[0061] According to the data in Table 2, we can get:
[0062] 1. Comparing Examples 01-02 and Comparative Example 01, the matte oil coatings of Examples 01-02 are resistant to aging, and the relative force of the laminated silicone protective film does not increase after aging, which is the result of the nano-PE wax, achieving an ideal effect;
[0063] 2. Comparing Examples 01-02 and Comparative Example 01, the relative strength of the silicone protective film of Examples 01-02 before aging is lower than that of the comparative example. This is because the surface energy of PE wax is low, and the surface energy of the coating is reduced after addition;
[0064] 3. Comparing Example 02, Example 03 and Comparative Example 04, although the added amounts are the same, the relative strength of the silicone protective film of Comparative Example 04 increases with aging. This is because the PE wax used in Comparative Example 04 has a large particle size, resulting in a rough coating surface, poor initial wetting of the silicone protective film, and low relative strength. It is only after aging that it is fully infiltrated and the relative strength increases. Nano-PE wax with a particle size D50 < 0.1 μm is preferred;
[0065] By comparing the test results of Example 01, Example 02, Comparative Example 01, Comparative Example 02, and Comparative Example 03, it can be concluded that adding too little PE wax will have no effect, while adding too much will cause the surface energy of the coating to be too low, which is not conducive to the bonding of the silicone protective film, and adding too much will cause the coating to fail the 100-grid test and the coating adhesion will deteriorate. The preferred addition amount of this experimental scheme is 9.1%-20% of the resin dosage.
[0066] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0067] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An environmentally friendly water-based aging-resistant matte coating, characterized in that: The components by weight include the following substances: 46-68 parts of solvent; Resin 15-35 parts; PE wax emulsion 5-12 parts; 3-5 parts of defoaming agent; Dispersant 0.5-2 parts; 2.5-6 parts of matting powder; Thickener 3-6 parts; Cross-linking agent 5-8 parts.
2. The environmentally friendly water-based aging-resistant matte coating according to claim 1, characterized in that: The particle size D50 of the PE wax emulsion is 0.1 μm.
3. The environmentally friendly water-based aging-resistant matte coating according to claim 1 is characterized by: The solvent is deionized water.
4. The environmentally friendly water-based aging-resistant matte coating according to claim 1 is characterized by: The matting powder is fumed silica.
5. The environmentally friendly water-based aging-resistant matte coating according to claim 1, characterized in that: The thickener is water-based polyurethane.
6. The environmentally friendly water-based aging-resistant matte coating according to claim 1, characterized in that: The cross-linking agent is a water-based isocyanate curing agent.
7. A matte black single-sided tape, characterized in that: The invention is prepared from any one of the environmentally friendly water-based aging-resistant matte coatings as described in claims 1 to 6.
8. A method for preparing a matte black single-sided adhesive tape, for preparing the matte black single-sided adhesive tape as claimed in claim 7, characterized in that: The steps include: S1, preparation of matt oil slurry: select quantitative polyester resin 1 and polyester resin 2, add solvent butanone and cyclohexanone, stir at a speed of 1100r / min for 25min; then add modified silica, stir at a speed of 1100r / min for 25min; after stirring evenly, use a sand mill to sand grind for 1-3H. During the sand grinding process, regularly take samples to test the particle size. When the particle size reaches the required specification, stop sand grinding to obtain matt oil slurry; S2, applying corona on the surface of a black substrate with a thickness of 0.05 mm, with the corona power set to 2 kW; applying the obtained matte oil slurry on the surface of the black substrate by micro-concave or gravure process to obtain a matte black anti-scratch coating film; S3, transferring a 25 μm acrylic film onto the 50 μm silicone release film, and laminating the film onto the non-matt oil coating surface of the matt black anti-scratch coating film, thereby obtaining a matt black anti-scratch tape; S4, placing the obtained matte black anti-scratch tape in a constant temperature chamber at 50° C. for curing for 72 hours to obtain a finished product.
9. The method for preparing a matte black single-sided adhesive tape according to claim 8, characterized in that: The substrate is a black PET or PI film.
Citation Information
Patent Citations
Exhaust matte black single-sided adhesive tape
CN212894553U